Effect of High Temperature Steam Sterilization Temperature on Flavor Quality of Tourism Food Gushi Goose Nuggets - Yang YU; Zhou ZHOU; Meng CAO; Junyue HE; Ying ZHOU (Shipin gongye ke-ji)
To investigate the effects of high-temperature steam sterilization (121, 126, and 134 ℃) on volatile components and aroma characteristics of Gushi goose nuggets: A characteristic Xinyang tourism food product, sensory evaluation coupled with headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) were used. Partial least squares discriminant analysis (PLS-DA), relative odor activity value (ROAV), and principal component analysis (PCA) were utilized to assess variations in sensory attributes and volatile compound profiles across experimental groups: non-sterilized control (M0), 121 ℃ sterilized (M1), 126 ℃ sterilized (M2), and 134 ℃ sterilized (M3). The results showed that the treatment group at 121 ℃ (M1) was closest to the control group (M0) in terms of aroma, taste, color, and tissue state. A total of 99 volatile components were identified in the four groups of samples, with significant differences in their types and contents. Based on PLS-DA, 33 characteristic components with variable importance in the projection (VIP>1) were screened, and the discriminant prediction accuracy of the model for the sterilization temperature reached 97.3%. ROAV analysis indicated that the ROAV of aldehydes in the treatment group at 134 ℃ (M3) was significantly higher than that in other groups, resulting in the strongest overcooked flavor. In contrast, the group sterilized at 121 ℃ had the largest variety of characteristic flavor substances, with a richer fatty, fruity, and fresh aroma, and no obvious off-flavors were produced. The PCA results showed that when the sterilization temperature exceeded 121 ℃, the dominant volatile components shifted from alcohols to aldehydes, significantly enhancing the fatty aroma. The comprehensive analysis demonstrated that high-temperature steam sterilization at 121 ℃ could not only maintain the aroma characteristics of Gushi goose nuggets to those of the unsterilized sample but also promoted the release of flavor substances and avoid the generation of overcooked off-flavors. These results provide a theoretical basis for the optimization of processing technology and the improvement of tourist food quality.